2018
DOI: 10.1039/c7cp06724k
|View full text |Cite
|
Sign up to set email alerts
|

Predicting anisotropic thermal displacements for hydrogens from solid-state NMR: a study on hydrogen bonding in polymorphs of palmitic acid

Abstract: The hydrogen-bonding environments at the COOH moiety in eight polycrystalline polymorphs of palmitic acid are explored using solid-state NMR. Although most phases have no previously reported crystal structure, measured 13C chemical shift tensors for COOH moieties, combined with DFT modeling establish that all phases crystallize with a cyclic dimer (R22(8)) hydrogen bonding arrangement. Phases A2, Bm and Em have localized OH hydrogens while phase C has a dynamically disordered OH hydrogen. The phase designated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
64
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(65 citation statements)
references
References 72 publications
(120 reference statements)
1
64
0
Order By: Relevance
“…[19] XRD suffers,h owever, from being insensitive to low atomic number (Z) nuclei, such as hydrogen;h ence,i ns ome cases,t he structural models produced by XRD are not sufficiently accurate for understanding how the resulting chemistry is directed by coordination. [20] Creative efforts in the emerging field of NMR crystallography [21][22][23][24][25] have pushed the use of NMR as ac omplementary tool for the elucidation of precise atomic coordinates,especially protons,int he unit cell.NMR crystallography,c ombines NMR, XRD,a nd computational chemistry, [26][27][28][29][30][31][32][33] to resolve atomic positions within crystals.Astrength of this scheme is using NMR chemical shifts and dipolar couplings between nuclei to validate ab initio quantum calculations for refining atom positions that are invisible to XRD. [34][35][36] Generally,i sotropic chemical shifts (d iso )a re used to identify spin-1/2 (nuclear spin, I = 1/2) NMR active species in structures,b ecause they are the most readily observed in NMR spectra.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[19] XRD suffers,h owever, from being insensitive to low atomic number (Z) nuclei, such as hydrogen;h ence,i ns ome cases,t he structural models produced by XRD are not sufficiently accurate for understanding how the resulting chemistry is directed by coordination. [20] Creative efforts in the emerging field of NMR crystallography [21][22][23][24][25] have pushed the use of NMR as ac omplementary tool for the elucidation of precise atomic coordinates,especially protons,int he unit cell.NMR crystallography,c ombines NMR, XRD,a nd computational chemistry, [26][27][28][29][30][31][32][33] to resolve atomic positions within crystals.Astrength of this scheme is using NMR chemical shifts and dipolar couplings between nuclei to validate ab initio quantum calculations for refining atom positions that are invisible to XRD. [34][35][36] Generally,i sotropic chemical shifts (d iso )a re used to identify spin-1/2 (nuclear spin, I = 1/2) NMR active species in structures,b ecause they are the most readily observed in NMR spectra.…”
mentioning
confidence: 99%
“…[19] XRD suffers,h owever, from being insensitive to low atomic number (Z) nuclei, such as hydrogen;h ence,i ns ome cases,t he structural models produced by XRD are not sufficiently accurate for understanding how the resulting chemistry is directed by coordination. [20] Creative efforts in the emerging field of NMR crystallography [21][22][23][24][25] have pushed the use of NMR as ac omplementary tool for the elucidation of precise atomic coordinates,especially protons,int he unit cell.…”
mentioning
confidence: 99%
“…Given the importance of correctly positioned hydrogen atoms for describing hydrogen bonding arrangements, independent experimental evidence from a technique that is sensitive to hydrogen atom positioning would be highly desirable. Nuclear magnetic resonance (NMR) spectroscopy is highly sensitive to the local environment about the nuclei studied (for example, effective anisotropic displacement parameters derived from NMR chemical shis have been estimated to be consistently smaller than those associated with X-ray diffraction 7,8 ). "NMR crystallography" 9 is a rapidly developing eld that has recently been recognised by the IUCr in the form of a commission on NMR crystallography.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27] More recent work has also demonstrated that NMR shifts can reliably predict crystal structures [28][29][30][31] and provide estimates of uncertainties in individual atomicp ositions. [32,33] To understand the nature and strength of the intra-dimer bonding in b and d-[TTF···TCNE] the 13 Cs hift tensors, reported here for the first time, are compared to previously reported benchmark experimental data for TTF, [TTF] 2 2 + + , [19] TCNE, [TCNE] 2 2À ,and [TCNE] 2À . [13] Previously,atheoretical study has evaluated the validity of the proposedl ong multi-center bonds in the a, b and d phases of [TTF···TCNE].…”
Section: Introductionmentioning
confidence: 99%